Scale Related Efficiencies as a (Minor) Source of the Profits-Market Share Relationship - Allen, Robert F.; Hagin, Allan Scott (The Review of Economics and Statistics, 1989)
A relative direct cost measure of scale economies is developed to examine the hypothesis that market share increases profits through the benefits of scale economies. Minor support is found for the hypothesis. Copyright 1989 by MIT Press.